2003
DOI: 10.1086/374972
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Rubella Virus Isolated during a Period of Epidemic Transmission in Italy, 1991–1997

Abstract: To study the molecular epidemiology of rubella virus during endemic transmission, phylogenetic analysis of the nucleotide sequence of the E1 gene was done with 31 isolates collected in northern Italy during 1991-1997, a period spanning 3 epidemics. The viruses segregated into distinct genotypic strains. Cocirculation of genotypic strains was detected; however, each epidemic was associated with specific strains, and strain displacement occurred concomitantly with each epidemic. Although most of the viruses from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…In terms of rapidity of the replicon-based assay, although cells inoculated with clinical specimens were incubated for 6 to 7 days before transfection with RUBrep/GFP-⌬NotI transcripts to duplicate the virus isolation procedures used previously (11), we have found that cultures inoculated with clinical specimens can be transfected 2 days postinoculation with GFP expression detectable 1 day posttransfection, for a total assay time of 3 days (W.-P. Tzeng, preliminary observations). In addition to virus detection, we showed that the novel replicon-based assay described here is also useful for virus genotyping, which remains a necessary part of the surveillance component of vaccination programs to determine virus distribution and transmission patterns (8,11,22,23). The E1 gene has been used for all molecular epidemiology studies done on RUB thus far, although the region of the E1 gene used in these studies has not been standardized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of rapidity of the replicon-based assay, although cells inoculated with clinical specimens were incubated for 6 to 7 days before transfection with RUBrep/GFP-⌬NotI transcripts to duplicate the virus isolation procedures used previously (11), we have found that cultures inoculated with clinical specimens can be transfected 2 days postinoculation with GFP expression detectable 1 day posttransfection, for a total assay time of 3 days (W.-P. Tzeng, preliminary observations). In addition to virus detection, we showed that the novel replicon-based assay described here is also useful for virus genotyping, which remains a necessary part of the surveillance component of vaccination programs to determine virus distribution and transmission patterns (8,11,22,23). The E1 gene has been used for all molecular epidemiology studies done on RUB thus far, although the region of the E1 gene used in these studies has not been standardized.…”
Section: Discussionmentioning
confidence: 99%
“…The E1 gene has been used for all molecular epidemiology studies done on RUB thus far, although the region of the E1 gene used in these studies has not been standardized. Sensitive RT-PCR assays developed for direct RUB detection in clinical specimens produce amplicons of 125 to 300 nt (3,(14)(15)(16)(17)24), shorter than the 600-to 1,400-nt amplicons generated from virus isolates used for genotyping (8,11,22,23), although recently a nested RT-PCR assay producing an ϳ500-nt amplicon directly from clinical specimens that could potentially be used for both detection and genotyping was reported (6,21). From cultures inoculated with clinical specimens shown to be positive for RUB by GFP expression after RUBrep/GFP-⌬NotI transfection, we RT-PCR amplified an ϳ500-nt window previously reported to be optimal for genotyping (22) that was RUB genome specific since it did not overlap with the replicon sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The rubella virus genome is ~10,000 nucleotides and encodes five protein products, including three virion proteins: the C or capsid protein and two envelope glycoproteins, E1 and E2. The E1 gene sequence has been used for genotyping and phylogenetic analysis of rubella virus isolates (2)(3)(4)(5)(6). To date Rubella viruses from Europe, Asia, and North America have been shown for the most part to group in a single genotype (Rubella Genotype I "RGI") that has a maximum diversity at the nucleotide level of ~5%.…”
Section: Introductionmentioning
confidence: 99%
“…To date Rubella viruses from Europe, Asia, and North America have been shown for the most part to group in a single genotype (Rubella Genotype I "RGI") that has a maximum diversity at the nucleotide level of ~5%. However, a limited number of viruses from Asia, Europe and Africa, formed a distant phylogenetic branch, differing from RGI viruses by 8% to 10%, which was designated Rubella Genotype II (RGII) (4,5,7,8). These two genotypes (RGI and RGII) belong to the single rubella virus serotype (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation